FACULTY-STUDENT MENTORSHIP PROGRAM FOR PRE-CLINICAL MEDICAL STUDENTS AT CHITWAN MEDICAL COLLEGE, NEPAL: A TEACHER’S PERSPECTIVE - Timilsina, Sameer (Journal of Chitwan Medical College, 2024)
Mentorship program has become a proven educational strategy in the context of contemporary medical education. The idea of mentorship is based on personal relationship in a professional setting where the mentor helps the mentee in realizing their full potential in attaining both personal and professional goals. The individualized guidance and support provided to the students not only enhances academic knowledge but also creates lasting relations and nurtures confidence and character. This viewpoint aims to shed light on the commendable initiatives taken by Chitwan Medical College on Faculty-Student Mentorship program tailored for preclinical undergraduate medical-students in their journey through medical school. The program is designed to help students navigate the early challenges of medical school and provide them with guidance and support to develop their professional identity.